Design and testing of planting unit for rice dry-direct-seeding planter in cold region - Zhao, Jiale; Zhang, Chengliang; Wei, Yanpeng; Guo, Mingzhuo; Chen, Chao; Zhang, Chongqin; Zhang, Yungan (International Journal of Agricultural and Biological Engineering, 2023)
Rice dry-direct-seeding technology is a time-saving, cost-saving and efficient rice cultivation technique that increases the efficiency of seeding. In order to implement the specialization, light simplicity and scale of rice production, improve the level of mechanization of the whole rice production process, and solve the problems of uneven seed furrows, uneven number of seeds sown, shallow mulching and uncompact repression that occur during the promotion and application of dry-direct-seeding for rice in the cold region of northeast China. In this paper, a planting unit for rice dry-direct-seeding planter is designed. The working principles and structural parameters of the furrow opening components, the seeding apparatus and the soil covering-pressing device are described. The mechanical model of the key components of the seeding unit was established, and the forward speed, roller diameter and compacting strength were selected as the test factors. A three-factor, five-level quadratic rotation orthogonal combination test was conducted with the seed breakage rate, seeding depth qualification rate, seeding uniformity coefficient of variation and hole grain count qualification rate as the evaluation indexes. Field performance test and test results show that: at a forward speed of 4 km/h, a roller diameter of 427 mm and a compacting strength of 48.45 kPa, the seed breakage rate was 1.31%, the sowing depth qualification rate was 9.95%, the coefficient of variation of sowing uniformity was 3.75% and the number of holes was 86.75%. This accords with the agronomic requirements of dry-direct-seeding for rice and implements a combination of superior agronomy and modern farm machinery. Keywords: rice, dry-direct-seeding, planting unit, structural design, testing research DOI: 10.25165/j.ijabe.20231604.7843 Citation: Zhao J L, Zhang C L, Wei Y P, Guo M Z, Chen C, Zhang C Q, et al. Design and testing of planting unit for rice dry-direct-seeding planter in cold region. Int J Agric & Biol Eng, 2023; 16(4): 76-84